A conceptual framework for patient-directed knowledge tools to support patient-centred care: Results from an evidence-informed consensus meeting. Issue 10 (October 2019) - Dreesens, Dunja; Stiggelbout, Anne; Agoritsas, Thomas; Elwyn, Glyn; Flottorp, Signe; Grimshaw, Jeremy; Kremer, Leontien; Santesso, Nancy; Stacey, Dawn; Treweek, Shaun; Armstrong, Melissa; Gagliardi, Anna; et al.
Highlights: Many knowledge tool types directed at patients exist, but these are poorly defined. This variety in different tool types poses challenges for developers and users. We provide a framework to clarify types, purposes and core elements of these tools. Such a framework may support deciding when to develop or to use which tool type. Abstract: Objective: Patient-directed knowledge tools are designed to engage patients in dialogue or deliberation, to support patient decision-making or self-care of chronic conditions. However, an abundance of these exists. The tools themselves and their purposes are not always clearly defined; creating challenges for developers and users (professionals, patients). The study's aim was to develop a conceptual framework of patient-directed knowledge tool types. Methods: A face-to-face evidence-informed consensus meeting with 15 international experts. After the meeting, the framework went through two rounds of feedback before informal consensus was reached. Results: A conceptual framework containing five patient-directed knowledge tool types was developed. The first part of the framework describes the tools' purposes and the second focuses on the tools' core elements. Conclusion: The framework provides clarity on which types of patient-directed tools exist, the purposes they serve, and which core elements they prototypically include. It is a working framework and will require further refinement as the area develops, alongside validation with a broader group of stakeholders. Practice implications: The framework assists developers and users to know which type a tool belongs, its purpose and core elements, helping them to develop and use the right tool for the right job.